2013
DOI: 10.1074/jbc.m113.451567
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Motif Ligases Catalyze Polyubiquitin Chain Formation through a Cooperative Allosteric Mechanism

Abstract: Background: Targeted degradation by tripartite motif (TRIM) ligase-catalyzed polyubiquitin chain formation is critical for cell regulation and innate immunity. Results: TRIM32-catalyzed chain formation requires oligomerization and uses a cooperative allosteric mechanism. Conclusion: Kinetics suggest TRIM32 assembles polyubiquitin chains as E2-linked thioesters prior to en bloc target protein transfer. Significance: A general mechanism for degradation signal assembly is revealed for the TRIM ligase superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 73 publications
4
49
0
Order By: Relevance
“…A recent kinetic study supports a model in which TRIM32, TRIM25 and TRIM5α catalyse poly‐ubiquitin chain formation through a cooperative allosteric mechanism, which would explain the requirement of oligomerization for catalytic activity (Streich et al , 2013). However, TRIM5α showed the lowest Hill coefficient in that study, which is intriguing given that TRIM5α forms higher order oligomers in contrast to the dimeric and tetrameric forms of TRIM25 and TRIM32, respectively.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A recent kinetic study supports a model in which TRIM32, TRIM25 and TRIM5α catalyse poly‐ubiquitin chain formation through a cooperative allosteric mechanism, which would explain the requirement of oligomerization for catalytic activity (Streich et al , 2013). However, TRIM5α showed the lowest Hill coefficient in that study, which is intriguing given that TRIM5α forms higher order oligomers in contrast to the dimeric and tetrameric forms of TRIM25 and TRIM32, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…TRIM ligases dimerize through their coiled‐coil region, and self‐association has been proposed to be a requirement for catalytic activity (Streich et al , 2013), though a systematic analysis of the relationship between oligomerization and catalytic activity is currently missing. In addition, there have been suggestions that substrate binding might induce higher order oligomers that may further enhance activity (Yudina et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although our studies focus on the behavior of Nrdp1 in cultured cells, a recent publication highlights the importance of TRIM protein self-association for polyubiquitin chain formation in vitro (49). The authors of this study demonstrated that oligomerization of the RING domain of TRIM32 is necessary to drive autoubiquitination, although they did not directly implicate the coiled-coil domain in the process of oligomerization.…”
Section: Discussionmentioning
confidence: 82%
“…Human recombinant E2 proteins Ubc2b (UBE2B), Ubc5A (UBE2D1), Ubc5B (UBE2D2), Ubc5C (UBE2D3), UbcH6 (UBE2E1), UbE2E2 (UBE2E2), UbcM2 (UBE2E3), and UbcH7 (UBE2L3) were those described previously (39). The Ubc5BC85S and Ubc5BC85A mutants were generated from pGEX4T1-HsUbc5B using the QuikChange site-directed mutagenesis kit (Agilent) and were individually sequenced to confirm the mutation and the absence of cloning artifacts.…”
Section: Generation and Purification Of Recombinant E2 Paralogs-mentioning
confidence: 99%
“…The resulting extract was centrifuged at 100,000 ϫ g for 45 min. The GST-IpaH9.8 fusion protein was purified from the 100,000 ϫ g supernatant by glutathione-Sepharose affinity chromatography (39). The isolated fusion protein was processed with 50 units/ml thrombin (GE Life Sciences) to remove the GST moiety.…”
Section: Generation and Purification Of Recombinant E2 Paralogs-mentioning
confidence: 99%